here is the two equation 1st=2x-y-3=0 and second=4x-y-5=0.How to solve this two equation by sbstituting method?

Asked by ketagajjar | 13th Aug, 2010, 01:21: PM

Expert Answer:

2x - y - 3 = 0
y = 2x - 3 
and now put this for y in second equation,
4x - y - 5 = 0
4x - (2x - 3) - 5 = 0
2x - 2 = 0
x = 1,
and hence y = 2x1 - 3 = -1
Regards,
Team,
TopperLearning.

Answered by  | 13th Aug, 2010, 01:45: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.